Strategic Development and Competitiveness of RoseStreet : An Independent Music Business - Nekovář, Jiří; Kupec, Václav; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis examines how RoseStreet, an independent music business, can develop strategically and remain competitive. It provides a comprehensive analysis of the company’s internal resources and external environment, and proposes strategies for sustainable growth and innovation. Using a qualitative case study approach, the study applies strategic frameworks (SWOT, VRIO, Porter’s Five Forces, and STP) to evaluate RoseStreet’s position. The analysis reveals that RoseStreet’s bundled service model, strong brand engagement, and agile team culture provide a competitive edge in serving independent artists. Growth is constrained by limited resources, service scalability and a reliance on its founder. Recommendations include developing scalable digital products to create recurring revenue streams, improving organizational effectiveness, and leveraging community elements to lead the growing independent artist market. The study concludes that with targeted innovation and proactive strategy, small creative businesses can compete in an industry dominated by global players.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses